Bases for a work programme to strengthen Latin American and Caribbean economic relations with Japan (SELA CaracasVE, 1993)
Presents suggestions on a medium-term work programme aimed at strengthening economic relations with Japan, on how it would operate and concerning the institutions that could take part in the programme.
DC